Mechanism of Gastroprotection by Bismuth Subsalicylate Against Chemically Induced Oxidative Stress in Cultured Human Gastric Mucosal Cells - Bagchi, Debasis; McGinn, Thomas R.; Ye, Xumein; Balmoori, Jaya; Bagchi, Manashi; Stohs, Sidney J.; Kuszynski, Charles A.; Carryl, Owen R.; Mitra, Sekhar (Digestive diseases and sciences, 1999)
Reactive oxygen species (ROS) are implicated in the pathogenesis of chemically induced gastric mucosal injury. We have investigated the effects of ethanol, hydrochloric acid (HCl), and sodium hydroxide (NaOH) on: (1) enhanced production of ROS including superoxide anion and hydroxyl radicals, (2) modulation of intracellular oxidized states by laser scanning confocal microscopy, and (3) DNA fragmentation, indices of oxidative tissue, and DNA damage in a primary culture of normal human gastric mucosal cells (GC), which were isolated and cultured from Helicobacter pylori-negative endoscopic biopsies from human subjects. The induction of ROS and DNA damage in these cells following exposure to ethanol (15%), HCl (150 mM) and NaOH (150 mM) were assessed by cytochrome c reduction (superoxide anion production), HPLC detection for enhanced production of hydroxyl radicals, changes in intracellular oxidized states by laser scanning confocal microscopy, and DNA damage by quantitating DNA fragmentation. Furthermore, the protective ability of bismuth subsalicylate (BSS) was assessed at concentrations of 25, 50, and 100 mg/liter. Incubation of GC with ethanol, HCI, and NaOH increased superoxide anion production by approximately 8.0-, 6.1-and 7.1-fold and increased hydroxyl radical production by 13.3-, 9.6-, and 8.9-fold, respectively, compared to the untreated gastric cells. Incubation of GC with ethanol, HCl, and NaOH increased DNA fragmentation by approximately 6.7-, 4.3-, and 4.8-fold, respectively. Approximately 20.3-, 17.5-, and 13.1-fold increases in fluorescence intensities were observed following incubation of gastric cells with ethanol, HCl, and NaOH, respectively, demonstrating dramatic changes in the intracellular oxidized states of GC following exposure to these necrotizing agents. Preincubation of GC with 25, 50, and 100 mg/liter of BSS decreased ethanol-induced increases in intracellular oxidized states in these cells by 36%, 56%, and 66%, respectively, demonstrating a concentration-dependent protective ability by BSS. Similar results were observed with respect to BSS in terms of superoxide anion and hydroxyl radical production, and DNA damage. The present study demonstrates that ethanol, HCl, and NaOH induce oxidative stress and DNA damage in GC and that BSS can significantly attenuate gastric injury by scavenging these ROS.